Pruritus, Allergy and Autoimmunity: Paving the Way for an Integrated Understanding of Psychodermatological Diseases? - Ferreira, Bárbara Roque; Pio-Abreu, José Luís; Figueiredo, Américo; Misery, Laurent (Frontiers in Allergy, 2021)
Pruritus is a key symptom in allergology and dermatology, contributing to the global and huge impact on quality of life related to skin disorders, both those which are not related to a primary dermatosis (illness) and those which are linked with primary skin lesions (disease). This is particularly evident within psychophysiological dermatoses, a group of psychodermatological diseases where there is a primary dermatosis, where psychological stress plays a role, and where pruritus may represent a major and shared symptom. The etiopathogenesis of pruritus in those disorders sheds light on the link among psychopathological features, psychological stress and the subtle interface between allergic and autoimmune mechanisms, where mast cells play a pivotal role. This review intends to look into the updated evidence on the shared biological mechanisms between allergy and autoimmunity, underlining pruritus as a core element, then revisiting the key role of mast cells and discussing the connection with melatonin and immune-inflammatory pathways in the physiopathology of psychophysiological dermatoses, thus paving the way for the understanding of their psychosomatic correlates and a comprehensive psychodermatological approach.